The Fucino 250–170 ka tephra record: New insights on peri-Tyrrhenian explosive volcanism, central mediterranean tephrochronology, and timing of the MIS 8-6 climate variability. (15th November 2022) - Monaco, Lorenzo; Leicher, Niklas; Palladino, Danilo M.; Arienzo, Ilenia; Marra, Fabrizio; Petrelli, Maurizio; Nomade, Sebastien; Pereira, Alison; Sottili, Gianluca; Conticelli, Sandro; D'Antonio, Massimo; Fabbrizio, Alessandro; et al.
Abstract: The Fucino Basin, central Italy, with its long and continuous history of Quaternary sediment accumulation, is one of the richest Mediterranean Middle Pleistocene tephra records. Here, we present a new detailed investigation of tephra layers (tephras) of the 250–170 thousand years before present (ka) interval, corresponding to the entire Marine Isotope Stage (MIS) 7 and parts of the MIS 8 and MIS 6. The investigated tephras have been characterised in terms of major, minor and trace elements, Sr–Nd isotopic compositions and 40 Ar/ 39 Ar ages. For correlation purposes, glass compositions and several new 40 Ar/ 39 Ar ages of selected proximal pyroclastic units spanning the same temporal interval from Vulsini (Latera Volcanic Complex), Sabatini, and Vico volcanic systems, central Italy, were measured. The late MIS 8-early MIS 6 Fucino tephras were backtracked to their corresponding volcanic sources, which include the Vulsini, Vico, Sabatini, Roccamonfina, Ischia and Campi Flegrei volcanic systems. While some of these tephras have been correlated to specific eruption units, other layers are currently not documented or described in near-vent sections, thus highlighting previously unrecognised events generated by these volcanic systems. Furthermore, the new high precision 40 Ar/ 39 Ar ages provide improved temporal constraints for Fucino making it one of the most detailed and chronologically best constrained tephra records for central Mediterranean MIS 7 tephrochronology. The Fucino record thus provides new integrative information for reconstructing the explosive history of Italian volcanoes during the investigated time interval. Furthermore, the geochronological constraints provide the basis for future paleoclimatic investigations at local and regional scale. Highlights: Fucino proves to be the richest Mediterranean Middle Pleistocene tephra record. The Fucino provides a detailed history of the explosive volcanism during MIS 7. High precision 40 Ar/ 39 Ar ages constrain the Mediterranean MIS 7 tephrochronology. A robust, independent age-model for the MIS 7 paleoclimatic record is provided.